Hubungan antara Media Sosial terhadap Peluang Kemenangan Pasangan Calon Gubernur DKI Jakarta Pada Pilkada 2017 (Studi Wilayah Jakarta Utara) - Raenaldy, Aldy; Erviantono, Tedi; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2017)
The study aims to determine the relations between social media to the chances of winning the candidate pairs of governors of DKI Jakarta in the first round election 2017 in North Jakarta Region. As a research frame, author use New Public Sphere theory by Karssen Mossberger. The method in this research is descriptive quantitative. The research instrument is a questionnaire which distributed to 400 respondents with a MoE of 5%. Determination of respondents using Multi-Stage Random Sampling technique. Based on the research, the author founds are: 85% of people in North Jakarta have social media and 335 respondents agree that social media can influence the chances of victory of candidate pair of governor of DKI Jakarta in elections 2017. Based on these findings, it can be concluded that social media can positively influence on the chance of winning the candidate pair of governor of DKI Jakarta in the 2017 election.   Keywords: Governor, New Public Sphere, Social Media